2016
DOI: 10.1083/jcb.201506081
|View full text |Cite|
|
Sign up to set email alerts
|

Negative regulation of phosphatidylinositol 3-phosphate levels in early-to-late endosome conversion

Abstract: C. elegans SORF-1 and SORF-2 and their mammalian homologs WDR91 and WDR81 maintain appropriate PtdIns3P levels in early-to-late endosome conversion by forming a complex with the Beclin1 subunit of the PI3K complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
98
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(114 citation statements)
references
References 59 publications
15
98
1
Order By: Relevance
“…Although WDR81 was earlier suggested being an integral membrane spanning protein (69), both our bioinformatic and biochemical ( Figure 3B) analysis suggest that WDR81 is cytosolic and it associates with EEA1 positive and LAMP1 positive endosomal membranes. This is in agreement with the recent findings of Liu et al (72) who showed the association/colocalization of WDR81 with EEA1-and Rab7-positive endosomes.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Although WDR81 was earlier suggested being an integral membrane spanning protein (69), both our bioinformatic and biochemical ( Figure 3B) analysis suggest that WDR81 is cytosolic and it associates with EEA1 positive and LAMP1 positive endosomal membranes. This is in agreement with the recent findings of Liu et al (72) who showed the association/colocalization of WDR81 with EEA1-and Rab7-positive endosomes.…”
Section: Discussionsupporting
confidence: 94%
“…Our data suggest that the WDR81-WDR91 complex is required for the trafficking and degradation of internalized PM proteins and facilitates delivery of cargo from early to late endosomal/lysosomal compartments. Our findings are consistent with a recent report from Liu et al (72), published during preparation of our manuscript, which identified the Caenorhabditis elegans orthologues of WDR81 and 91 (respectively F25C9.1 or SORF-2 and ZK563.5 or SORF-1), as genes required for partial rescue of the endosome/lysosome fusion defects present in coelomocytes of C. elegans vps18 mutants and showed that mammalian WDR81 and WDR91 form a complex functioning in endolysosomal trafficking.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings thus reveal a conserved mechanism by which PtdIns3P synthesis is inhibited to allow for the change of lipid identity that accompanies early‐to‐late endosome conversion (Figure ). In addition, these findings provide important insights for understanding the role of WDR81 in cerebellar ataxia, mental retardation and disequilibrium syndrome (CAMRQ2), which is associated with WDR81 mutation …”
Section: Endo‐lysosomal Traffickingmentioning
confidence: 98%
“… While the mechanism governing the Rab5‐to‐Rab7 switch was revealed a few years ago, it remains largely elusive how correct endosomal PtdIns3P levels are achieved to allow for endosome conversion and the change of endosome lipid identity. Recently, C.Y.’s lab identified SORF‐1/WDR91 and SORF‐2/WDR81, 2 novel factors conserved from C elegans to mammals, as essential regulators of PtdIns3P in early‐to‐late endosome conversion . In.…”
Section: Endo‐lysosomal Traffickingmentioning
confidence: 99%